Applied Psychological Elements and the Professional Role of the Guidance Counsellor in Modern Education - Hoxter, Lee (Canadian Journal of Counselling and Psychotherapy, 2012)
School counselors soon become out of touch with Applied Psychology even though they function daily in the behavioral science com- ponent of the education process. The modern counselor is urged to re- examine his role and image as a professional with special skills that are valuable to teachers and pupils. A review is attempted to re-acquaint the counselor with some current notions of professional role clarifications